The Concept of Triple Helix Mohammad Natsir and its Implementation in Strengthening Religious Character Education - Rizal Firdaus; Kama Abdul Hakam; Momod Abdul Somad; Ahmad Syamsu Rizal (STAI Miftahul Ula Nganjuk, 2020)
This article aims to discuss the concept of triple helix Mohammad Natsir which he often refers to as the three pillars of Muslims’ power and associate it with the idea Kampus Merdeka and Merdeka belajar to strengthen the education of religious characters at the university level. A method that uses a qualitative approach with data sourced library data. This article's result is the concept of triple helix mohamad Natsir namely the integration of education between three institutions, masjid, pesantren and campuses. Among the cooperation programs that can be done are internship programs, making humanitarian projects, teaching, and researching potential mosques or pesantren. In order for this program to run according to the plan in advance must agree on the concepts and purpose of education, agree to the integration and conversion of the curriculum, and monitoring and evaluation periodically.